KAKAOBRIK: PEMANFAATAN LIMBAH KULIT KAKAO MENJADI BRIKET - Awaluddin, Awaluddin (Departemen Teknologi Pertanian Universitas Hasanuddin, 2025)
Community Service Learning (CSL) is one of the three pillars of higher education that must be carried out by all students as a primary requirement for graduation to achieve a bachelor's or diploma degree. Therefore, students must be prepared to adapt to the community to provide direct services in implementing the programs that have been designed. Based on the observations conducted, one of the potentials possessed by Rea Village is cocoa plantations. In the cocoa production process, cocoa husks are not utilised and end up as waste. This cocoa husk waste is simply left in the plantations or in residents' yards without being utilised. Cocoa husks themselves can be utilised to make briquettes. Therefore, to address the issue of cocoa husk waste, an innovation in the form of cocoa husk briquettes has been introduced. With cocoa husk briquettes, this can serve as a solution for waste management, an alternative energy source for the community, and a new economic potential for the community.